Common Subdivisions of Dewey Decimal Classification Editions 12-19: A Comparative Study - Asundi, A. Y. (Journal of Information and Knowledge, 1980)
Presents a comparative study of the different editions of Dewey Decimal Classification Studies,include idea plane aspects such as additions of new standard subdivisions, revision of the scope of divisions, relation of existing subdivisions, verbal plane aspects such as terminological currency and consistency. Highlights the predictions of classifiers in the adoption of the revised versions of DDC in respect of standard subdivisions.